Miracles from Heaven [videorecording (DVD)]. - Garner, Jennifer, 1972-; Rogers, Kylie, 2004-; Henderson, Martin, 1974-; Queen Latifah, 1970-; Riggen, Patricia (Sony Pictures Home Entertainment, 2016)
Based on the incredible true story of the Beam family. When Christy discovers her ten-year-old daughter Anna has a rare, incurable disease, she becomes a ferocious advocate for her daughter's healing as she searches for a solution. After Anna has a freak accident and falls three stories, a miracle unfolds in the wake of her dramatic rescue that leaves medical specialists mystified, her family restored and their community inspired.